Karakteristik Visual Gambar Hewan Realistis Karya Anak Usia 10-11 Tahun - Emalia Destianti; Rahina Nugrahani; Hasti Rahmaningtyas (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
This study is motivated by the importance of understanding the visual characteristics of drawings produced by children aged 10–11 years within the context of non-formal learning. Children’s drawings not only represent objects but also reflect stages of visual development and learning experiences. This research draws upon theories of children’s artistic development and visual analysis in fine arts. The study employs a descriptive qualitative method with a visual analysis approach. The subjects consist of children aged 10–11 years who participate in private drawing lessons. Data were collected through observation, documentation of students’ artworks, and brief interviews with the instructor. The findings indicate that variations in drawing outcomes are influenced by the duration of learning, practice habits, and the teaching methods applied. Furthermore, the study reveals that children’s ability to produce simple realistic drawings is shaped by their learning experiences and instructional guidance during the learning process, resulting in diverse visual characteristics that remain within a developmental stage.